2017
DOI: 10.1002/polb.24529
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and viscoelastic properties of confined amorphous polymers

Abstract: Confinement of polymers to nanoscale dimensions can dramatically impact their physical properties. Substantial efforts have focused on the glass transition temperature (T g ) of polymers confined to thin films, but their mechanical properties are less studied despite their technological importance. In this review, challenges with mechanical measurements of polymer thin films are discussed along with novel metrologies that provide insight into their mechanical properties. A comparison of experimental measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 231 publications
0
43
0
Order By: Relevance
“…The nanoconfinement effect has a strong influence on the T g . Inspired by the pioneering work of Jackson and McKenna on the T g depression for the organic liquids confined in nanopores, the T g of polymers in the nanometer scales has received significant interest . The T g of thin films, defined by a simple nanoconfined physical model, has been characterized by different types of measurements, including dynamic, thermodynamic, and pseudothermodynamic (see subsequently for the definitions).…”
Section: Glass Transition For Polymersmentioning
confidence: 99%
“…The nanoconfinement effect has a strong influence on the T g . Inspired by the pioneering work of Jackson and McKenna on the T g depression for the organic liquids confined in nanopores, the T g of polymers in the nanometer scales has received significant interest . The T g of thin films, defined by a simple nanoconfined physical model, has been characterized by different types of measurements, including dynamic, thermodynamic, and pseudothermodynamic (see subsequently for the definitions).…”
Section: Glass Transition For Polymersmentioning
confidence: 99%
“…In comparison with bulk films of the same polymer, thin films of linear, freely deposited polymers that are a few tens of nanometers thick may exhibit significantly different properties, for example, glass transition temperature ( T g ), fragility, and stiffness among others. [ 1–48 ] For instance, in comparison with a bulk polystyrene (PS) film and as measured by ellipsometry, a 21‐nm‐thick, substrate‐supported high molecular weight (MW) PS film exhibits a T g reduction of 10°C. [ 18 ] Understanding such nanoscale T g ‐confinement effects in polymers is important for many advanced technological applications, for example, thin films used in nanolithography processes for microchip manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Our approach is based on the understanding of the dynamics of confined polymers built over the last 20 years from experimental measurements, theories and simulations. Vogt, 28 and references therein, has provided a good review on the significant impact of the confinement of amorphous polymers in nanoscale dimensions on their mechanical properties. Many authors [29][30][31][32] have revealed that the glass transition temperature T g of thin polymer films strongly interacting with a solid substrate increases with decreasing film thickness.…”
Section: Introductionmentioning
confidence: 99%